2013
DOI: 10.1098/rspb.2012.2363
|View full text |Cite
|
Sign up to set email alerts
|

Rain reverses diel activity rhythms in an estuarine teleost

Abstract: Activity rhythms are ubiquitous in nature, and generally synchronized with the day -night cycle. Several taxa have been shown to switch between nocturnal and diurnal activity in response to environmental variability, and these relatively uncommon switches provide a basis for greater understanding of the mechanisms and adaptive significance of circadian (approx. 24 h) rhythms. Plasticity of activity rhythms has been identified in association with a variety of factors, from changes in predation pressure to an al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 45 publications
1
44
0
Order By: Relevance
“…For ectotherms that inhabit seasonally distinct temperate and subtropical zones, telemetry is showing how species use movements to compensate for localized environmental fluctuations. For example, estuarine yellow fin bream (Acanthopagrus australis) exhibit intricate behavioral switches, reversing depth distributions and diel activity patterns as a result of heavy rainfall and severe changes in turbidity and salinity (44).…”
Section: Movements Of Aquatic Animals In Four Dimensionsmentioning
confidence: 99%
“…For ectotherms that inhabit seasonally distinct temperate and subtropical zones, telemetry is showing how species use movements to compensate for localized environmental fluctuations. For example, estuarine yellow fin bream (Acanthopagrus australis) exhibit intricate behavioral switches, reversing depth distributions and diel activity patterns as a result of heavy rainfall and severe changes in turbidity and salinity (44).…”
Section: Movements Of Aquatic Animals In Four Dimensionsmentioning
confidence: 99%
“…Acceleration was sampled at 5 Hz for 120 s on each axis, with a measurement range of ±3.34 m s 2 . Acceleration was calculated as a root mean square value from each axis, and recorded data were transmitted every 190-290 s. Averaging acceleration (over 2 min) in this way precludes identification of the absolute frequency of specific behaviours, so our biologging data represent relative, voluntary activity levels across the temperatures the fish experienced (after Payne et al, 2011;Payne et al, 2013), and we refer to these data as 'activity' hereafter. Five Vemco VR2W receivers recorded activity data from the transmitters within the study site, and these were spaced ~500 m apart.…”
Section: Methodsmentioning
confidence: 99%
“…While normal and reverse DVM is the dominant rhythm in basking shark behavior, depth loggers have also shown that tidal rhythms influence vertical migrations in this species, again a likely reflection of shifting zooplankton fields (Shepard et al, 2006). Acceleration and depth transmitters implanted into yellowfin bream, Acanthopagrus australis, found that normally diurnal bream consistently switched to a nocturnal lifestyle in the days following rainfall, and this was interpreted in the context of a potential shift in energetic status (Payne et al, 2013). In a test of the effects of ecotourism on natural behavior, depth loggers were attached to the caudal peduncle of free-ranging whitetip reef sharks, Triaenodon obesus, at a popular recreational dive site (Fitzpatrick et al, 2011).…”
Section: Diel Rhythm Plasticitymentioning
confidence: 99%
“…When attached to animals, accelerometers can record acceleration in one, two or three spatial axes simultaneously and at high sampling frequencies. For loggers, the accelerometer device generally must be retrieved to acquire data (Houghton et al, 2009;Watanabe et al, 2012), whereas transmitters require remote detection of acceleration data summaries by receivers (Payne et al, 2011;Payne et al, 2013). This represents a major trade-off: loggers will provide data at far greater resolution, but need to be retrieved and are generally larger; transmitters are often smaller and do not need to be retrieved, but provide summaries of acceleration measurements rather than raw values.…”
Section: Biologgingmentioning
confidence: 99%